Protein–polysaccharide interactions at fluid interfaces - Rodríguez Patino, Juan Miguel; Pilosof, Ana M.R. (Food hydrocolloids, 2011)
Protein–polysaccharide interactions find many applications in food engineering and new food formulations. This review article describes recent research on the effect of protein–polysaccharide interactions on the properties of air–water and oil–water interfaces, as affected by their behaviour in the bulk phase. The interfacial behaviour of protein–polysaccharide mixtures exhibiting associative (i.e., net attractive) interactions as well as their performance in food emulsions and foams has been the subject of several reviews in the last decade. Much less attention has been paid to the interfacial behaviour of protein–polysaccharide mixtures exhibiting unfavourable interactions. Thus we are concerned here with the interfacial behaviour of both kinds of mixtures. The cartoon is of different mechanisms involved in the adsorption and/or interactions between biopolymers (proteins, surface-active polysaccharides (SA-PS), and non-surface-active polysaccharides (non-SA-PS). [Display omitted]